Impact of Opioid Consumption in Patients With Functional Gastrointestinal Disorders - Melchior, Chloé; Desprez, Charlotte; Wuestenberghs, Fabien; Leroi, Anne-Marie; Lemaire, Antoine; Goucerol, Guillaume (Frontiers in Pharmacology, 2020)
Objective: We aimed to determine the burden of opioid consumption in a cohort of patients with functional gastrointestinal disorders. Methods: All patients diagnosed with functional gastrointestinal disorders and referred to our university hospital were evaluated from 2013 to the beginning of 2019. Irritable bowel syndrome and functional dyspepsia diagnoses were determined according to Rome criteria and severity according to irritable bowel syndrome severity scoring system. Vomiting was quantified using a 5-point Likert scale, and constipation severity was measured using the Knowles-Eccersley-Scott-Symptom questionnaires. Quality of life was quantified by the GastroIntestinal Quality of Life Index. Patients were categorized as being treated on a chronic basis with either tramadol, step II opioids, step III opioids or as being opioid-free. Results: 2933 consecutive patients were included. Patients had irritable bowel syndrome, functional dyspepsia or a combination of both in 37.3%, 64.2 % and 24.8% respectively. Among them, the consumption of tramadol, step II (tramadol excluded) and step III opioids was 1.8, 1.3 and 0.3 % respectively in 2013 and 4.3, 3.4 and 1.9% in 2018 (p<0.03). Opioid consumption was associated with increased vomiting (p=0.0168), constipation (p<0.0001), symptom severity (p<0.001), more altered quality of life (p<0.0001) and higher depression score (p=0.0045). Conclusion: In functional gastrointestinal disorders, opioid consumption has increased in the last years and is associated with more GI symptoms (vomiting, constipation and GI severity), higher depression and more altered quality of life.